O Canadá na rota das migrações internacionais: brasileiros em Quebec - Fraga, Marcus Vinicius (2013)
This work presents the migration of Brazilians to Quebec. By studying the immigration in Quebec under the context of Canadian asymmetrical federalism, we seek to understand what gave rise to the immigration policy of the French-Canadian province. We aim to have the theoretical support needed to understand the reasons why middle-class Brazilians are attracted to Quebec. After applying socioeconomical questionnaires and qualitative interviews, we believe that social reasons a poor quality of public services, urban violence, and doughts about the Brazilian political system have developed this flow